Faktor Risiko Kejadian Dismenore Primer Pada Siswi di SMK PGRI 1 Jakarta Timur - Resty Hermawahyuni; Sarah Handayani; Rony Darmawansyah Alnur (Jurnal Kesehatan Komunitas, 2022)
Primary dysmenorrhea is an incident experienced by adolescent girls, usually during the first menstruation (menarche), without any specific disease cause. The cause of primary dysmenorrhea is due to the increased production of prostaglandins from the endometrium during menstruation. This study aimed to determine the factors associated with the incidence of primary dysmenorrhea in female students at the Vocational High School (SMK) of the Indonesian Teachers Association (PGRI) 1 East Jakarta. The research design used was cross-sectional, with a stratified random sampling proportional sampling technique. The population in this study were students of SMK PGRI 1 Jakarta, with a total sample of 201 students. Data analysis using chi-square test. The results showed that there were 115 female students (57.2%) experiencing primary dysmenorrhea. Bivariate analysis showed that there was a significant relationship between age of menarche (p-value = 0.002), family history (p-value = 0.001), and fast-food habits (p-value = 0.000) with the incidence of primary dysmenorrhea. Meanwhile, there was no significant relationship between the length of menstruation (p-value = 0.226) and physical activity (p-value = 0.478) with the incidence of primary dysmenorrhea. It is recommended that the students of SMK PGRI 1 East Jakarta reduce the habit of eating fast food considering the study results that found a significant relationship between fast eating habits and the incidence of primary dysmenorrhea.